Age-Related Changes in the Human Thymus Gland: A Comparative Study of 70 Specimens - Shahid Kamran, Muhammad Yousuf Khoso, Saleem Ahmed Bhutto, Irfan Ul Akbar, Imran Mehboob Baig, Syed Irfan Raza Arif (Pakistan Journal of Medical & Health Sciences, 2024)
Background: The thymus gland is a central organ for the development of T-cells, integral to the immune system. Its function significantly changes with age, leading to alterations in immune response, a phenomenon referred to as thymic involution. Objective: This study investigates the structural and functional alterations in the thymus gland of 70 specimens from individuals across various age groups to identify the effects of aging on thymic morphology and function. Methods: A total of 70 human thymus specimens were collected from individuals ranging from newborns to individuals over 70 years of age. Tissue samples were analyzed for size, weight, histology, and immune function. Immunohistochemistry and T-cell quantification were used to assess the presence of thymocytes and thymic epithelial cells. Results: The study found a significant decline in thymic size, cellular composition, and thymocyte production with age. In older individuals, thymic tissue was largely replaced by adipose tissue, and the medullary region exhibited reduced cellular organization. T-cell output was found to be drastically reduced in individuals over 60. Conclusion: The thymus undergoes substantial morphological and functional decline with aging, contributing to immunosenescence. These findings underline the importance of maintaining thymic function and suggest potential therapeutic strategies for thymic rejuvenation in elderly populations. Keywords: Thymus gland, age groups, T-Cell Quantification